The PedPAD study: boys predominate in the hypogammaglobulinaemia registry of the ESID online database. (June 2014) - Schatorjé, E. J. H.; Gathmann, B.; van, R. W. N. M.; de, E.; ,; Alsina, L; Baumann, U; Belohradsky, BH; Bienemann, K; Boardman, B; Borte, M; Bredius, RG; et al.
Summary Hypogammaglobulinaemias are the most common primary immunodeficiency diseases. This group of diseases is very heterogeneous, and little is known about these diseases in children. In the Pediatric Predominantly Antibody Deficiencies (PedPAD) study, we analysed data from the European Society for Immunodeficiencies (ESID) online database to gain more insight into the characteristics of children with hypogammaglobulinaemia; 46 centres in 18 different countries agreed to participate. Data from 2076 of the 3191 children who were registered at the time of data extraction with a diagnosis of hypogammaglobulinaemia (this excludes agammaglobulinaemia and defects in class‐switch recombination) were available for analysis. The data set showed several limitations. Because of country‐related differences in diagnostic criteria used for the classification of different types of primary hypogammaglobulinaemia, further analysis of the data was performed in the combined data set. The most striking observation is the strong majority of male patients in the group of children with primary hypogammaglobulinaemia (n = 1292, 63%). This male predominance was observed in each of the 18 countries involved. The boys were younger at diagnosis (mean age males 5·3 years; mean age females 5·8 years). Moreover, one or more complications were more frequently reported in boys (12%) compared to girls (5%). The male predominance suggests that patients with an undetected or unknown X‐linked genetic cause are included in this group of children registered as primary hypogammaglobulinaemia.